Reduced emissions and fuel consumption in automobile engines - Schäfer, Fred (Springer-Verlag ; SAE International, 1995)
Introduction - Causes of pollutants and their toxicity - Design features which influence pollant emissions and fuel consumption in four-engines - Engine-related measures which reduce pollutant emissions and consumption in two-strokes - Exhaust aftertreatment methods - The influence of fuel and lubricants on emissions and fuel consumption - Problems with CO2 emissions - Laws regulations the emissions of pollutants and maximum fuel consumption of combustion engines.